2018
DOI: 10.1088/1361-6528/aaabe1
|View full text |Cite
|
Sign up to set email alerts
|

Integrated nanomaterials for extreme thermal management: a perspective for aerospace applications

Abstract: Nanomaterials will play a disruptive role in next-generation thermal management for high power electronics in aerospace platforms. These high power and high frequency devices have been experiencing a paradigm shift toward designs that favor extreme integration and compaction. The reduction in form factor amplifies the intensity of the thermal loads and imposes extreme requirements on the thermal management architecture for reliable operation. In this perspective, we introduce the opportunities and challenges e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 84 publications
0
21
0
Order By: Relevance
“…Nanotechnology has the potential to revolutionise our future, offering life-saving or climateprotecting applications and being part of a multitude of current technological developments from aerospace technologies to food packaging and cosmetics (Nafisi and Maibach, 2017;Barako et al, 2018;Pereda et al, 2018). Failure of nanotechnology to realise its potential is inconceivable in terms of a financial and social impact, and yet, this prospect is not unlikely.…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology has the potential to revolutionise our future, offering life-saving or climateprotecting applications and being part of a multitude of current technological developments from aerospace technologies to food packaging and cosmetics (Nafisi and Maibach, 2017;Barako et al, 2018;Pereda et al, 2018). Failure of nanotechnology to realise its potential is inconceivable in terms of a financial and social impact, and yet, this prospect is not unlikely.…”
Section: Introductionmentioning
confidence: 99%
“…Shamberger and Fisher [104] indicated that PCM composite nano-architectures have a higher thermal conductivity than PCMs alone. The greater conductivity of 2–5% ofAl 2 O 3 helps achieve a larger thermal accessible volume, which minimizes the overheating of the devices [106]. The addition of the nanocomposite in PCMs is a handy technique to equally distribute the heat and enhance the aircraft safe operation during lightning strikes.…”
Section: Nanotechnology Applications In Transportation Vehiclesmentioning
confidence: 99%
“…Boiling enhancements through modified surfaces promise performance breakthroughs for applications ranging from power generation to desalination and thermal management for high-power electronics and nuclear reactors. − The latent heat of nucleate pool boiling promises up to 2 orders of magnitude higher in heat flux dissipation in comparison to single-phase liquid cooling . Extensive studies have explored various strategies to enhance boiling performances by investigating different types of surfaces or architectures.…”
Section: Introductionmentioning
confidence: 99%